GAMBARAN KONDISI PSIKOSOSIAL MASYARAKAT LERENG MERAPI PASCA 6 TAHUN ERUPSI GUNUNG MERAPI - Purborini, Nurul (Jurnal Keperawatan Muhammadiyah, 2016)
Objective: To describe psychosocial condition in community who lives near Merapi Mountain Methods: It was descriptive study using cross-sectional method. This study was using questionnaire to collect psychosocial data. The questionnaire was Impact of Event Scale Results: Respondents in this study were 50 people. Based on result, 74% of respondents had mild trauma and 58% of respondents were women. Around 12 respondents (24%) were in late elderly. In the experiences of trauma, women had higher number than men.  Conclusion: in 6 years after Merapi Mountain’s eruption, there are still some psychosocial problems that happen in community who lives near Merapi Mountain.